2016
DOI: 10.1111/jopy.12264
|View full text |Cite
|
Sign up to set email alerts
|

Happy Now, Tired Later? Extraverted and Conscientious Behavior Are Related to Immediate Mood Gains, but to Later Fatigue

Abstract: Extraverted and conscientious behavior predict mental depletion after a 3-hour delay. The results help reconcile previous findings regarding the consequences of state Extraversion and provide novel information about the consequences of state Conscientiousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 46 publications
6
55
3
Order By: Relevance
“…Missing ESM reports are a rather common problem in ESM research. Our compliance rate was at the lower end of the range of similar studies (Fleeson, 2001(Fleeson, , 2007Howell et al, 2017;Leikas & Ilmarinen, 2017;McCabe & Fleeson, 2016;Wilt et al, 2012;Wilt et al, 2017). Although one study indicated that missing reports are not be associated with ESM-relevant variables (Sun, Rhemtulla, & Vazire, 2019), the implications of missing reports in ESM research are currently not yet well understood.…”
Section: Limitationsmentioning
confidence: 69%
“…Missing ESM reports are a rather common problem in ESM research. Our compliance rate was at the lower end of the range of similar studies (Fleeson, 2001(Fleeson, , 2007Howell et al, 2017;Leikas & Ilmarinen, 2017;McCabe & Fleeson, 2016;Wilt et al, 2012;Wilt et al, 2017). Although one study indicated that missing reports are not be associated with ESM-relevant variables (Sun, Rhemtulla, & Vazire, 2019), the implications of missing reports in ESM research are currently not yet well understood.…”
Section: Limitationsmentioning
confidence: 69%
“…In addition, the mean levels of repeated measures should also correlate with independent trait measures of extraversion to further validate the consistency criterion. Findings from repeated measurements of the extraverted behavior of multiple individuals demonstrate that there are indeed robust individual differences in mean levels of extraverted behaviors, but these also tend to be less consistent than behaviors that are relevant for other "Big Five" traits (Catterson, Eldesouky, & John, 2017;Heller, Komar, & Lee, 2007;Leikas & Ilmarinen, 2017;Sun, Stevenson, Kabbani, Richardson, & Smillie, 2017;Wilt, Bleidorn, & Revelle, 2017). Moreover, support for a correlation between individual mean levels of behaviors and independent trait measures is mixed (Heller et al, 2007;Leikas & Ilmarinen, 2017), perhaps owing to the smaller sample sizes that are typical in experience sampling research.…”
Section: Consistency Over Time and Situationsmentioning
confidence: 97%
“…The literature has offered less evidence that extraverts attain and maintain higher popularity because they enjoy being sociable. For example, studies have demonstrated that no differences exist between extraverts' and introverts' enjoyment of typically extraverted behaviors (Fleeson, Malanos, & Achille, 2002;Leikas & Ilmarinen, 2017;Wilt, Noftle, Fleeson, & Spain, 2012). Moreover, social activity may be a generally more peripheral constituent of extraversion, especially compared to reward sensitivity (Lucas et al, 2000) or social attention (Ashton et al, 2002).…”
Section: Does Extraversion Predict Popularity?mentioning
confidence: 99%
“…In the rest of this paper, we will consider other ways of operationalizing these metrics to answer different types of questions raised in the larger within- However, we are not always interested in simple fluctuations or oscillations of a single variable. Often, we are interested in approximating how something measured at one point influences something that happens later, such as current Extraversion and Conscientiousness predicting both future boosts in positive affect as well as fatigue (Leikas & Ilmarinen, 2017). In such cases, one can investigate cross-lagged autoregressive effects, in which one lagged variable (X1,t-1) is regressed on another variable (X2,t), which tests whether a previous personality state predicts a second state at the present moment.…”
Section: Within-person Variability 27mentioning
confidence: 99%